2006
DOI: 10.1021/pr060306q
|View full text |Cite
|
Sign up to set email alerts
|

A Top-Down/Bottom-Up Study of the Ribosomal Proteins of Caulobacter crescentus

Abstract: Ribosomes from the gram-negative α-proteobacterium Caulobacter crescentus were isolated using standard methods. Proteins were separated using a two-dimensional liquid chromatographic system that allowed the analysis of whole proteins by direct coupling to an ESI-QTOF mass spectrometer and of proteolytic digests by a number of mass spectrometric methods. The masses of 53 of 54 ribosomal proteins were directly measured. Protein identifications and proposed post-translational modifications were supported by prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 83 publications
3
57
0
Order By: Relevance
“…Proteomic studies of bacterial ribosomal proteins have reported di-or monomethylation at this residue in E. coli (29), Caulobacter crescentus (28), and Rhodopseudomonas palustris (27), and the reported molecular mass of Thermus thermophilus RpL7/L12 also suggests methylation (26). However, this modification appears not to be present in all bacteria as Bacillus subtilis RpL7/L12 was found to be unmodified (45).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies of bacterial ribosomal proteins have reported di-or monomethylation at this residue in E. coli (29), Caulobacter crescentus (28), and Rhodopseudomonas palustris (27), and the reported molecular mass of Thermus thermophilus RpL7/L12 also suggests methylation (26). However, this modification appears not to be present in all bacteria as Bacillus subtilis RpL7/L12 was found to be unmodified (45).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that each species has a unique complement of modifications, and despite the availability of many genomic sequences, MS analysis of isolated ribosomes remains the only way to completely characterize the spectrum of modifications for a new species. In the proteomic study of Caulobacter crescentus, some modifications similar to those observed in E. coli were observed, as well as some novel species-specific modifications [8]. The ability to map modifications in the ribosomal proteome will permit the study of changes in modifications with growth conditions or genotype, which may elucidate the specific role of ribosomal protein modifications in assembly or translation.…”
Section: Applications Of Mass Spectrometrymentioning
confidence: 91%
“…The composition of the ribosomal proteome from Caulobacter crescentus was determined using a combination of MS analysis of intact proteins and of proteolytic fragments [8]. The masses of most of the ribosomal proteins were determined directly, and sequences were confirmed by MS-MS analysis of tryptic peptides.…”
Section: Applications Of Mass Spectrometrymentioning
confidence: 99%
“…Mass spectrometry (MS) has become an indispensable tool for protein sequence mapping [1,2]. This is usually done by using a top-down or a bottom-up proteomic approach [1][2][3][4][5][6][7][8][9][10][11][12]. In the top-down method, a protein ion is dissociated in a tandem mass spectrometer (MS/MS) and the fragment ions generated are interpreted to generate a stretch of amino acid sequence information.…”
mentioning
confidence: 99%
“…However, this is a time-consuming process and there is no guarantee that the peptides produced from the multiple digestions will cover the entire sequence of a protein. In some cases, the combination of top-down and bottom-up methods is used to increase sequence coverage [4,7,12]. …”
mentioning
confidence: 99%